Epiphyseal Fusion of Radius and Ulna at Wrist Joint in Male and Female in the Population of Lahore – An Age Estimation Criterion (Medical Forum Monthly, 2024)
Objective: To ascertain the age of maturity from x-rays of wrist joint in the population of Lahore.Study Design: Observational / cross sectional StudyPlace and Duration of Study: This study was conducted at the Postgraduate Medical Institute/Ameer ud Din Medical College in the Department of Forensic Medicine & Toxicology Lahore General Hospital, Lahore from Jan-Dec 2017.Materials and Methods: One hundred (100) patients reporting to radiology department of LGH between age group of 13 years to 21 years were included in this study, and these x-rays were reported by a radiologist of the hospital regarding the state of union of epiphysis of lower end of radius and ulna bones.Results: Most of the people belong to Muslim religion (97%) of the total 100 reported to the General Hospital, Lahore. In females, age group of 13-15 years consisted 24% of the total cases in which 9 cases reported at stage II in which center appeared but no union found and 3 cases has early union. In age group 16-18 years, one case recorded in stage II and 9 cases were recorded at stage III in which early union appeared and 6 cases were recorded at stage IV in which complete union appeared in age group 19-21 years, only one case placed in stage III and 21 cases were placed in stage IV in which complete union was found. In males, age group of 13-15 years consisted 20% of the total cases in which 5 cases reported at stage II in which center appeared but no union found and 3 cases has early union. In age group 16-18 years, one case recorded in stage II and 11 cases were recorded in stage III in which early union appeared and 5 cases were recorded in stage IV in which complete union appeared and age group 19-21 years, 23 cases were placed at stage IV in which complete union found.Conclusion: This study proved that x-rays of wrist joint can be used as an important tool for maturity assessment in the your of Lahore and it is consistent with the previous studies.